Sustained release of targeted cardiac therapy with a replenishable implanted epicardial reservoir. (June 2018) - Whyte, William; Roche, Ellen; Varela, Claudia; Mendez, Keegan; Islam, Shahrin; O'Neill, Hugh; Weafer, Fiona; Shirazi, Reyhaneh; Weaver, James; Vasilyev, Nikolay; McHugh, Peter; Murphy, Bruce; et al.
Abstract The clinical translation of regenerative therapy for the diseased heart, whether in the form of cells, macromolecules or small molecules, is hampered by several factors: the poor retention and short biological half-life of the therapeutic agent, the adverse side effects from systemic delivery, and difficulties with the administration of multiple doses. Here, we report the development and application of a therapeutic epicardial device that enables sustained and repeated administration of small molecules, macromolecules and cells directly to the epicardium via a polymer-based reservoir connected to a subcutaneous port. In a myocardial infarct rodent model, we show that repeated administration of cells over a four-week period using the epicardial reservoir provided functional benefits in ejection fraction, fractional shortening and stroke work, compared to a single injection of cells and to no treatment. The pre-clinical use of the therapeutic epicardial reservoir as a research model may enable insights into regenerative cardiac therapy, and assist the development of experimental therapies towards clinical use. An epicardial device that enables sustained and repeated administration of small molecules, macromolecules and cells directly to the epicardium provides therapeutic benefits in a rat model of myocardial infarction.